The gene coding for carbamoyl-phosphate synthetase I was formed by fusion of an ancestral glutaminase gene and a synthetase gene. - Nyunoya, H (1985)
A near full-length cDNA copy of rat carbamoyl-phosphate synthetase I (EC 6.3.4.16) mRNA has been cloned. The cDNA insert in the recombinant plasmid pHN234 is 5.3 kilobases long. Analysis of the sequence coding for carbamoyl-phosphate synthetase I indicates that the gene has arisen from a fusion of two ancestral genes: one homologous to Escherichia coli carA, coding for a glutaminase subunit, and the second homologous to the carB gene that codes for the synthetase subunit. A short amino acid sequence previously proposed to be part of the active site involved in glutamine amide nitrogen transfer in the E. coli and yeast carbamoyl-phosphate synthetases (EC 6.3.5.5) is also present in the rat enzyme. In the mammalian enzyme, however, the glutaminase domain lacks a cysteine residue previously shown to interact with glutamine. The cysteine is replaced by a serine residue. This substitution could, in part, account for the inability of mammalian carbamoyl-phosphate synthetase I to catalyze the hydrolysis of glutamine to glutamic acid and ammonia.